Mendings - Sweeney, Megan, 1967- (Duke University Press, 2023)
"Through five formally distinct yet interlinked essays, Mendings tells an intimate story about family, selfhood, and the love and loss lodged in garments, and a broader story about clothes and mending as tools for navigating the vicissitudes of living. In dialogue with clothing lovers, fiber artists, evolutionary biologists, historians, and environmentalists, the book illuminates the crucial roles that clothing plays in enabling us to communicate; to cultivate relationships with ourselves and with others; to counter injustice and make meaning from violence and grief; and to experience the joys of creativity, artistry, and self-fashioning. In addition to featuring artwork by Nina Katchadourian, Elena Herzog, Celia Pym, Merrill Goldstein, Gali Cnaani and others, Mendings includes photographs of childhood letters, family artifacts, journal entries, and paintings and sketches by the author and her family."--